2023
DOI: 10.3389/fvets.2023.1174560
|View full text |Cite|
|
Sign up to set email alerts
|

Examination of critical factors influencing ruminant disease dynamics in the Black Sea Basin

Margarida Arede,
Daniel Beltrán-Alcrudo,
Jeyhun Aliyev
et al.

Abstract: IntroductionRuminant production in the Black Sea basin (BSB) is critical for national economies and the subsistence of rural populations. Yet, zoonoses and transboundary animal diseases (TADs) are limiting and threatening the sector. To gain a more comprehensive understanding, this study characterizes key aspects of the ruminant sector in nine countries of the BSB, including Armenia, Azerbaijan, Belarus, Bulgaria, Georgia, Moldova, Romania, Türkiye, and Ukraine.MethodsWe selected six priority ruminant diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It is worth noting that ruminant production is a critical livestock subsector in the majority of the studied countries [58][59][60][61][62][63][64][65][66][67]. In addition, areas found as suitable for anthrax by our model largely match rural settings where pastoralism is widely practiced [68], and livestock is the main source of subsistence for these populations [4,68]. Similarly, Carlson et al [6] suggested higher human anthrax risk in rural areas, and observed increased human and livestock anthrax vulnerability in rainfed systems across arid and temperate landscapes in the same region (Eurasia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that ruminant production is a critical livestock subsector in the majority of the studied countries [58][59][60][61][62][63][64][65][66][67]. In addition, areas found as suitable for anthrax by our model largely match rural settings where pastoralism is widely practiced [68], and livestock is the main source of subsistence for these populations [4,68]. Similarly, Carlson et al [6] suggested higher human anthrax risk in rural areas, and observed increased human and livestock anthrax vulnerability in rainfed systems across arid and temperate landscapes in the same region (Eurasia).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the disease is sporadic in animals, with a higher prevalence in southern Europe, and linked to historical foci in northern areas [2]. Across the Black Sea basin, as of 2023, anthrax remained endemic in Türkiye, Azerbaijan, Georgia, and Moldova, and it was reported sporadically in Bulgaria, Romania, Ukraine, Belarus [4], and the Russian Federation [5]. Even in endemic countries, surveillance systems for anthrax are limited, contributing to underreporting and gaps in understanding its geographic extent [6].…”
Section: Introductionmentioning
confidence: 99%